How A Locus Of Control, Financial Learning Quality, And Financial Self-Efficacy Affect Financial Management Behavior - Ulhaq, Nada Dhiya; Mediawati, Elis (Journal of Education Method and Learning Strategy, 2024)
The purpose of this study was to determine how the quality of financial learning of accounting students in Bandung City is influenced by locus of control, level of financial independence, and quality of financial learning. This research uses the Behavioral finance theory approach. The type of research chosen is quantitative descriptive method. The data collected for this study came from questionnaires distributed using purposive sampling method. A total of 100 respondents were undergraduate accounting students studying in Bandung in 2018 and 2019. Data analysis methods include multiple linear regression and IBM SPSS version 25. The results showed that the quality of financial learning and financial self-efficacy partially had a significant effect on financial management behavior, while locus of control had no significant effect on financial management behavior. However, simultaneously the quality of financial learning, financial self-efficacy, and locus of control have a significant effect on the financial management behavior of accounting students in Bandung City. It can be concluded that locus of control cannot influence students' financial management behavior without other variables or factors such as the quality of financial learning and financial self-efficacy.